Menelaah Sumber Dan Hakikat Ilmu Dalam Perspektif Al-Qur’an, Serta Mengkritisi Dikotomi Ilmu Agama Dan Ilmu Umum Secara Argumentatif - Alfa Rohmatin; Ropiul Anwar; Mch Wildan Hidayatuloh; Muhammad Hadis; Moch Haris Al-Qudsi; Rahmi Siti Rahmawati (PT. Nawa Edukasi Nusantara, 2026)
The dichotomy between religious knowledge and general knowledge remains a significant issue in contemporary Islamic education and epistemological discourse. This separation has created a fragmented understanding of knowledge, in which religious sciences are often associated only with ritual and spiritual matters, while general sciences are viewed as secular and detached from religious values. This study aims to examine the sources and nature of knowledge from the Qur’anic perspective and to critically analyze the dichotomy between religious and general sciences. This research uses a qualitative approach with a library research method. The data were collected through documentation by examining Qur’anic verses, tafsir literature, books on Islamic philosophy of science, and relevant journal articles. The data were analyzed using content analysis to identify key concepts, interpret meanings, and construct critical arguments. The findings show that knowledge in the Qur’an is rooted in revelation, reason, and empirical experience. These sources are not contradictory but complementary within a tawhidic framework. The nature of knowledge in Islam is not merely cognitive or technical, but also spiritual, ethical, and transformative. The study concludes that the dichotomy between religious and general sciences is inconsistent with the Qur’anic paradigm of knowledge. Therefore, Islamic education needs an integrative epistemological framework that connects revelation, reason, science, ethics, and human welfare.